Femoral Cartilage Thickness in Knee Osteoarthritis Patients and Healthy Adults: An Ultrasound Measurement Comparison - Rita Vivera Pane; Rahayu Setiyaningsih; Gunawan Widodo; Aufar Zimamuz Zaman Al Hajiri; Juwita Raudlatul Salsabil (The Scientific World Journal)
Background. Currently, conventional radiography is still widely used to diagnose knee osteoarthritis and assess the grade according to Kallgren and Lawrence’s criteria. Ultrasound is a simple, inexpensive, noninvasive, and dynamic modality for evaluating femoral cartilage (FC) thickness. This study aims to measure the FC thickness in knee osteoarthritis (OA) patients and compare it to healthy adults using ultrasound assessment. Methods. An observational study with a cross-sectional design was conducted at the Department of Physical Medicine and Rehabilitation of Hajj General Hospital, Surabaya, Indonesia, from May to July 2022. Participants radiologically diagnosed with OA were included in the study and assigned to the OA group. Meanwhile, healthy adults without knee symptoms were included in the control group. FC thickness was measured using ultrasound scans at three sites: medial condyle (MC), intercondylar (IC), and lateral condyle (LC) on both sides of the knee. Results. The mean age in the OA and control groups was 61.03 ± 8.6 and 33.93 ± 14.7 years, respectively. Most participants in both groups were female. The OA group exhibited a thinner FC (1.49–1.63 mm) than the control group (1.68–1.87 mm). There was a significant difference in the mean of the right and left MC in both groups (p<0.05) but no significant difference in the IC and LC. Conclusion. OA patients exhibited a thinner FC than healthy adults in the control group. There was a significant difference in the mean thickness of the MC between groups.